2014
DOI: 10.3109/15412555.2014.948995
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Increases the Ability of Roflumilast N-oxide to Inhibit Cigarette Smoke-Induced Epithelial to Mesenchymal Transition in Well-differentiated Human Bronchial Epithelial Cellsin vitro

Abstract: The PDE4 inhibitor roflumilast N-oxide acts (over)additively with simvastatin to prevent CSE-induced EMT in WD-HBEC in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…However, pretreatment of airway epithelial cells with dexamethasone was not sufficient to reverse TGFb-induced EMT (148). In addition to corticosteroids, Milara and colleagues (34,149,150) showed that treatment with cAMP-elevating compounds successfully restores airway epithelial barrier dysfunction induced by either cigarette smoke extract or TGF-b in vitro. Therefore, it will be of interest to study effects of PDE4 inhibitors on epithelial barrier dysfunction in COPD.…”
Section: Recent Developments In Therapeutic Approaches Based On the Rmentioning
confidence: 99%
“…However, pretreatment of airway epithelial cells with dexamethasone was not sufficient to reverse TGFb-induced EMT (148). In addition to corticosteroids, Milara and colleagues (34,149,150) showed that treatment with cAMP-elevating compounds successfully restores airway epithelial barrier dysfunction induced by either cigarette smoke extract or TGF-b in vitro. Therefore, it will be of interest to study effects of PDE4 inhibitors on epithelial barrier dysfunction in COPD.…”
Section: Recent Developments In Therapeutic Approaches Based On the Rmentioning
confidence: 99%
“…We found that ROS generation was significantly elevated in NPC cells when GLRX3 was knocked down (Figure 6B, 6C). The effect of ROS on activating the Akt pathway remains controversial [20, 21]. To identify whether the hypergeneration of ROS by silencing GLRX3 in NPC cell lines contributes to inhibiting the Akt signaling cascade, we decreased the ROS level in shGLRX3 -HONE1/CNE2 cells by an ROS inhibitor N-acetyl cysteine (NAC) (Figure 6D, 6E).…”
Section: Resultsmentioning
confidence: 99%
“…However, increased glutathione is not sufficient to overcome the increase of ROS in lung tissue [ 30 ]. In this regard, we and others showed that in different models relevant to pulmonary fibrosis roflumilast and its active metabolite roflumilast N-oxide reduce ROS generation in numerous types of lung cells and lung tissue [ 12 , 31 , 32 ]. Specifically, it has been shown that roflumilast inhibits the NADPH oxidase (NOX) activity by suppressing the interaction of rac1 with NADPH oxidase isoenzymes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we and others showed that in different models relevant to pulmonary fibrosis roflumilast and its active metabolite roflumilast N-oxide reduce ROS generation in numerous types of lung cells and lung tissue [ 12 , 31 , 32 ]. Specifically, it has been shown that roflumilast inhibits the NADPH oxidase (NOX) activity by suppressing the interaction of rac1 with NADPH oxidase isoenzymes [ 31 ]. Furthermore, roflumilast was able to reduce an enhanced expression of NADPH oxidase isoenzymes NOX1, NOX2 DUOX2 and NOX4 secondary to different stimuli in bronchial epithelial cells and lung fibroblast [ 11 , 32 ] which may contribute to the anti-fibrotic profile of roflumilast in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%